2022
DOI: 10.47162/rjme.62.2.04
|View full text |Cite
|
Sign up to set email alerts
|

Practical aspects regarding the histopathological grading and anaplastic transformation of gangliogliomas – a literature review

Abstract: Ganglioglioma represents a benign central nervous tumor, occurring predominantly in the pediatric population and affecting the temporal lobe. It is also renowned for its epileptogenic potential. However, to date, there are numerous uncertain features about this tumor, especially about its grading system. In the former World Health Organization (WHO) Classification of central nervous tumors system, gangliogliomas could have been attributed one out of three grades: grade I (benign), grade II (atypical), and grad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 59 publications
0
4
0
Order By: Relevance
“…The effect of radiation on this group of tumors was usually considered to be limited since most are low-grade neoplasms [ 5 ]. High-grade lesions, including anaplastic ganglioglioma, liponeurocytoma and some central/extraventricular neurocytomas, may require adjuvant radiation therapy, as supported by conflicting literature findings [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…The effect of radiation on this group of tumors was usually considered to be limited since most are low-grade neoplasms [ 5 ]. High-grade lesions, including anaplastic ganglioglioma, liponeurocytoma and some central/extraventricular neurocytomas, may require adjuvant radiation therapy, as supported by conflicting literature findings [ 19 , 21 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although a large retrospective meta-analysis showed that postoperative RT could significantly improve local control in patients with gangliogliomas who underwent STR, the benefit on overall survival (OS) was not observed [ 23 ]. Furthermore, many other studies reported that RT had little impact on progression-free survival (PFS) and OS [ 5 , 18 , 24 , 25 , 26 ]. A recent study by Lin and collaborators [ 4 ] showed that adjuvant RT may have a potentially adverse effect on survival in adult patients with low-grade gangliogliomas and that adjuvant chemotherapy has no positive effect on OS in operated patients.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations